Increased fibroblast telomerase expression precedes myofibroblast α-smooth muscle actin expression in idiopathic pulmonary fibrosis (Clinics, 2012)
OBJECTIVE: This study sought to identify the relationship between fibroblast telomerase expression, myofibroblasts, and telomerase-mediated regulatory signals in idiopathic pulmonary fibrosis. METHODS: Thirty-four surgical lung biopsies, which had been obtained from patients with idiopathic pulmonary fibrosis and histologically classified as usual interstitial pneumonia, were examined. Immunohistochemistry was used to evaluate fibroblast telomerase expression, myofibroblast α-smooth muscle actin expression and the tissue expression of inter leu kin-4, transforming growth factor-β, and basic fibroblast growth factor. The point-counting technique was used to quantify the expression of these markers in unaffected, collapsed, mural fibrosis, and honeycombing areas. The results were correlated to patient survival. RESULTS: Fibroblast telomerase expression and basic fibroblast growth factor tissue expression were higher in collapsed areas, whereas myofibroblast expression and interleukine-4 tissue expression were higher in areas of mural fibrosis. Transforming growth factor-β expression was higher in collapsed, mural fibrosis and honeycombing areas in comparison to unaffected areas. Positive correlations were found between basic fibroblast growth factor tissue expression and fibroblast telomerase expression and between interleukin-4 tissue expression and myofibroblast α-smooth muscle actin expression. Negative correlations were observed between interleukin-4 expression and basic fibroblast growth factor tissue expression in areas of mural fibrosis. Myofibroblast α-smooth muscle actin expression and interleukin-4 tissue expression in areas of mural fibrosis were negatively associated with patient survival. CONCLUSION: Fibroblast telomerase expression is higher in areas of early remodeling in lung tissues demonstrating typical interstitial pneumonia, whereas myofibroblast α-smooth muscle actin expression predominates in areas of late remodeling. These events seem to be regulated by basic fibroblast growth factor and interleukin-4 tissue expression, respectively.